CONCEPTUAL DIRECTIONS IN REGIONAL MANAGEMENT OF MUNICIPAL SOLID WASTE SPHERE - Pysarenko, P. V.; Samoilik, M. S.; Dychenko, O. Yu.; Ts’ova Yu. А.; Podliesnyi, A. V.; Tretyakova, D. M. (Scientific Progress & Innovations, 2021)
The problem of waste management is extremely topical for the regions of Ukraine. Landfills occupy valuable agricultural land resources. Unauthorized landfills cause special danger. At the same time, the issues of reducing contaminated lands area, their restoration and return to agricultural production are relevant for scientific research. The aim of our study was to argument scientifically the optimization model in municipal solid waste management sphere in the region aimed at balancing two economic and environmental criteria: economic damage for the environmental pollution and total expenses for the functioning of MSW handling sphere. The directions have also been determined for handling municipal solid waste in the context of realization of social, economic and environmental strategies and recommendations regarding the improvement of financial and economic support have been given. On the basis of the proposed model the optimal ratio of ecological and economic criteria for the development of waste management in Poltava region has been determined. It has been substantiated that the development of MSW management sphere should be aimed at resolving the priority issues of: providing environmentally safe MSW management at maximizing recycling and market development of recyclable materials, minimizing waste form ation. Solving these problems in the region should be performed in accordance with the main directions that are proposed to be carried out in three phases. The model will create the basis for determining strategic development directions in the given sphere within the implementation of social, economic and ecological strategy of the regional development. The conducted research is the basis for developing scientific principles and practical recommendations for the formation of a system for the restoration of contaminated areas and their return to agricultural production in Ukraine.